Estudo da produção de biossurfactantes sintetizados por Pseudomonas aeruginosa AP029-GVIIA utilizando manipueira como fonte de carbono - Bezerra, Márcio Silva (2012)
This study evaluates the biosurfactants production from cassava wastewater, an agro industrial residue, to be used as carbon source. Using a factorial design 24-1 (half fraction), 10 tests were performed using Pseudomonas aeruginosa AP029/GVII-A in submerged batch cultivation in rotating incubator (shaker). The influence of factors (temperature, agitation, aeration ratio and concentration of cultivation medium) at two different levels for the synthesis of the biosurfactant. Samples were collected throughout the cultivation by 132 hours of fermentation were completed. The best outcome was intended by following production through substrate consumption, dry matter, reduction of surface tension (ring method) and emulsification index. The kinetics of microorganism was assessed for the carbon source used. The results showed that the cassava wastewater is a well assimilable substrate for the production of biotensoactive, reaching 91 % of consumption by the micro-organism under study. The growth temperature was found to be one of the leading factors in the synthesis of the metabolite, followed by aeration and also due to the agitation. The best results showed a 30 % reduction in surface tension (% RTS) for the environment, reaching values of 30 mN/m; 3.0 g /L of biomass and emulsifying index greater than 65 %. The metabolite synthesized still remained stable for different salt concentrations (1, 5 and 10 % w/ v) and alkaline pH (8-10).